Biosystematic, Essential Oil, and Biological Activity Studies on Medicinal Plant Moluccella L. (Lamiaceae) Species from Turkey - Sancar, Pelin Yilmaz (Mdpi, 2025)
This study aims to determine the biosystematic (morphological, anatomical, palynological) characteristics of Moluccella (M. laevis and M. spinosa) species growing in Turkey, the components of their essential oil (EOs), and some of their biological activities (antimicrobial and radical scavenging capacity). In the biosystematic studies, morphological, anatomical, and palynological analyses were performed. The stem, leaf, flower, and seed characteristics of the plants, along with various ecological properties, were examined and the necessary measurements were taken and presented. In the anatomical studies, the root, stem, leaf, and petioles of the species were photographed under a light microscope to determine their anatomical features. Additionally, light microscope and scanning electron microscope studies were conducted to reveal the surface properties of pollen and seeds. The chemical composition of the EOs of the plant samples was analyzed by GC-MS (Gas Chromatography-Mass Spectrometry). The main components of the EOs of the examined species are alpha-thujene, beta-pinene, beta-caryophyllene, and 2-pentadecanone. Significant differences have been found in the EO component profiles of Moluccella laevis and Moluccella spinosa. While a total of 33 components were found in M. laevis, 59 components were detected in M. spinosa. The EO yield was higher in M. spinosa compared to M. laevis. The antimicrobial activity was tested using both disc diffusion and the MIC (minimum inhibitory concentration) methods. The results showed that the methanolic extracts prepared from the aerial parts of the plant samples exhibited varying levels of antimicrobial and antifungal activity against the tested microorganisms. The antioxidant capacity of the methanolic extract was measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging capacity. The DPPH radical scavenging capacity increased with the increasing concentrations of both plant extracts. Antimicrobial capacity was higher in M. spinosa, while radical scavenging capacity was higher in M. laevis. As a result of the obtained data, although the studied species share similar features, they exhibit significant differences in terms of morphological, anatomical, and palynological characteristics. The antimicrobial and radical scavenging capacities of the plants were noteworthy. The data obtained from this study, which are being presented for the first time in the literature, provide a valuable resource for researchers working on this genus.
Keywords: Moluccella; systematic; essential oil; antimicrobial; DPPH